Oncogenic roles of carbonic anhydrase IX in human nasopharyngeal carcinoma - Sang, Yi (e-Century Publishing Corporation, 2014)
Carbonic anhydrase IX (CA IX), a hypoxia-inducible protein in tumors, has been shown to be valuable for the prognosis of nasopharyngeal carcinoma (NPC). However, the function and mechanism of CA IX has been not explored in NPC. Here, we found that CA IX was detected at higher levels in NPC cells and tissues than their corresponding partners. Furthermore, the cell growth, migration and invasion in vitro were altered with shRNA or overexpression of CA IX in NPC cells. More importantly, the metastatic ability of NPC cells stably expressing CA IX was significantly enhanced using the hepatic metastasis model of nude mice in vivo. Finally, the mTOR pathway was indicated to be involved in such effects of CA IX on NPC. This is the first evidence that CA IX may promote the NPC metastasis to potentially be a therapeutic target for NPC, and that the inhibitory molecules of CA IX and/or the mTOR pathway alone or combination with both may be worth to have a clinical trial for the patients with NPC.